2023
DOI: 10.1021/acs.jafc.3c00743
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Reveals the Killing Mechanism by Which Entomopathogenic Fungi Manipulate the RNA Expression Profiles of Termites and Provides Inspiration for Green Pest Management

Abstract: As chemical pesticides have caused serious environmental pollution, fungus-based biological control has become a developing alternative to chemical control. Here, we aimed to determine the molecular mechanism underlying how Metarhizium anisopliae facilitated invasive infection. We found that the fungus increased its virulence by downregulating glutathione S-transferase (GST) and superoxide dismutase (SOD) throughout termite bodies. Among 13 fungus-induced microRNAs throughout termite bodies, miR-7885-5p and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Some fungi have been shown to actively enhance their virulence by reducing the expression of detoxification genes in their insect hosts. This manipulation could be a strategy employed by the pathogen to disrupt the insect's conventional detoxification mechanisms, making it more susceptible to infection and facilitating the success of fungal invasion [67]. A similar downregulation of detoxification genes has been observed in other insect-fungi interactions, such as in Drosophila melanogaster [22].…”
Section: Discussionmentioning
confidence: 68%
“…Some fungi have been shown to actively enhance their virulence by reducing the expression of detoxification genes in their insect hosts. This manipulation could be a strategy employed by the pathogen to disrupt the insect's conventional detoxification mechanisms, making it more susceptible to infection and facilitating the success of fungal invasion [67]. A similar downregulation of detoxification genes has been observed in other insect-fungi interactions, such as in Drosophila melanogaster [22].…”
Section: Discussionmentioning
confidence: 68%
“…It is shown that Metarhizium anisopliae increased its virulence by downregulation of glutathione Stransferase (GST) and superoxide dismutase (SOD) throughout termite bodies. 60 Our transcriptome data reveled that some GST genes (BBA_04201, BBA_07754, BBA_03339, and BBA_07410) were significantly downregulated in the ΔBbSre1 strain; however, its virulence was significantly decreased. We speculated that downregulated GSTs could not counteract effects of reduced growth, decreased adaptations to low-oxygen and oxidative stress, as well as the decreased lipid drops with reduced TAG storage and cell membrane homeostasis on the decreased fungal virulence.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, some virulence-associated genes, e.g., Chi3 , Bly5 , Mad1 , Hyd2 , and Fre2 , , were dramatically downregulated in the Δ BbSre1 strain as direct targets verified with EMSA, demonstrating a virulence regulator. It is shown that Metarhizium anisopliae increased its virulence by downregulation of glutathione S-transferase (GST) and superoxide dismutase (SOD) throughout termite bodies . Our transcriptome data reveled that some GST genes (BBA_04201, BBA_07754, BBA_03339, and BBA_07410) were significantly downregulated in the Δ BbSre1 strain; however, its virulence was significantly decreased.…”
Section: Discussionmentioning
confidence: 86%
“…Insect detoxification and antioxidant systems often function in conjunction with the immune system, which effectively reduces the risk of toxins and reactive oxygen species (ROS) during host–pathogen interactions (Syazwan et al, 2021). It has been verified that the fungus Metarhizium anisopliae increased its virulence by downregulating glutathione S‐transferase ( GST ) and superoxide dismutase ( SOD ) throughout termite bodies (Liu, Wang, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%